Pola Asuh Orang Tua Single Parents dalam Menanggulangi Kenakalan Remaja di Kelurahan Karang Maritim Kecamatan Panjang Bandar Lampung - Rudy Irawan (Jurnal Syntax Admiration, 2024)
The purpose of this study is to determine the parenting style applied by parents, especially Single Parents mothers in overcoming juvenile delinquency, the causes of juvenile delinquency, solutions to juvenile delinquency aged 12-18 years in Karang Maritim Village, Panjang District, Bandar Lampung City. The method used in this study is a descriptive qualitative method, which aims to describe and explain the state of the object under study as it occurs in the field. This research was conducted in Kelurahan Karang Maritim, Panjang District, Bandar Lampung. The subjects and informants in this study were mothers (single parents) and their teenage children aged 12-18 years. Data collection is carried out by observation to the field, interviews with informants, and documentation related to research. The results showed (1) Parenting styles in overcoming juvenile delinquency can be said to be less than optimal, due to parenting that is too restrictive (Authoritarian), as well as parenting that is too liberating (Permissive) so as to cause deviant behavior changes in the form of delinquency such as smoking, skipping school, brawling, returning home late at night for no apparent reason, saying dirty, and playing mobile phones until they forget the time, And there are few parents who use democratic parenting in educating children.